Lost in Time. Plot Complexities of Contemporary Russian Prose Fiction. Selected Examples .......... 591 - Brążkiewicz, Bartłomiej (Czas w kulturze rosyjskiej, 2019)
LOST IN TIME. PLOT COMPLEXITIES OF CONTEMPORARY RUSSIAN PROSE FICTION. SELECTED EXAMPLESOne of essential features distinguishing contemporary Russian prose fiction is a tendency to expose the absurdity of life. Present-day authors uncover the anomalous state of human existence as well as the one regarding the ambiguity of universal values by applying certain literary devices and various methods of narration – interior monologues, multiperspectivity, disturbed causality or rejecting the objectiveness of time and space. However, some writers prove that a postmodern expression in the field of Russian literature is not entirely inner-directed and hardly developed solely for its own sake. Out of many recent novels establishing similar framework this paper deals particularly with two of them: Sergey Arno’s Smiritel’naya rubashka dlya geniyev and Kovcheg by Egor Fetisov. Their characters, as set out in constructed realm, through altered states of consciousness cross from one parallel world to the other. As a consequence of being detached from any and everything, devoid of time points and landmarks, they seem to experience getting lost in time. Although such a complexity of fabula and syuzhet inclines the possibility of making the texts incomprehensible, the ideas revealed cause a reason to discover new paths for struggle against modern philosophical and cultural concepts shaping the individuals’ ecosystem.